Neutrophils promote hepatic metastasis growth through fibroblast growth factor 2–dependent angiogenesis in mice. Issue 6 (2nd May 2017) - Gordon‐Weeks, Alex N.; Lim, Su Y.; Yuzhalin, Arseniy E.; Jones, Keaton; Markelc, Bostjan; Kim, K. Jin; Buzzelli, Jon N.; Fokas, Emmanouil; Cao, Yunhong; Smart, Sean; Muschel, Ruth
Abstract : Hepatic metastases are amenable to ablation; however, many patients are not suitable candidates for such therapy and recurrence is common. The tumor microenvironment is known to be essential for metastatic growth, yet identification of plausible targets for cancer therapy in the microenvironment has proven elusive. We found that human colorectal cancer liver metastases and murine gastrointestinal experimental liver metastases are infiltrated by neutrophils. Plasticity in neutrophils has recently been shown to lead to both protumor and antitumor effects. Here, neutrophils promoted the growth of hepatic metastases, given that depletion of neutrophils in already established, experimental, murine liver metastases led to diminished metastatic growth. Decreased growth was associated with reductions in vascular density and branching suggestive of vessel normalization. Metastasis‐associated neutrophils expressed substantially more fibroblast growth factor 2 (FGF2) than naïve neutrophils, indicating neutrophil polarization by the tumor microenvironment. Administration of FGF2 neutralizing antibody to mice bearing experimental liver metastases phenocopied neutrophil depletion by reducing liver metastatic colony growth, vascular density, and branching. Conclusion : Here, we show, using FGF2 as an example, that identification of factors responsible for the protumoral effects of infiltrating myeloid cells can be used to target established liver metastases. Such therapies could be utilized to limit disease progression and potentiate the effects of standard ablative therapies. (Hepatology 2017;65:1920‐1935).